2006
DOI: 10.1007/s11426-006-2013-x
|View full text |Cite
|
Sign up to set email alerts
|

An unusual isotopic fractionation of boron in synthetic calcium carbonate precipitated from seawater and saline water

Abstract: Inorganic calcium carbonate precipitation from natural seawater and saline water at various pH values was carried out experimentally. The results show the clear positive relationships between boron concentration and δ 11 B of inorganic calcium carbonate with the pH of natural seawater and saline water. However, the variations of boron isotopic fractionation between inorganic calcite and seawater/saline water with pH are inconsistent with the hypothesis that B(OH) 4 − is the dominant species incorporated into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…They reasoned that the presence of Mg 2+ or other microelements was the main reason for this observation and concluded that the heavier B(OH) 3 species was incorporated preferentially into Mg(OH) 2 . The results of our study have further confirmed the conclusion of Xiao et al (2006a).…”
Section: The Manner In Which α D−fsw Changes With Ph Forsupporting
confidence: 89%
See 4 more Smart Citations
“…They reasoned that the presence of Mg 2+ or other microelements was the main reason for this observation and concluded that the heavier B(OH) 3 species was incorporated preferentially into Mg(OH) 2 . The results of our study have further confirmed the conclusion of Xiao et al (2006a).…”
Section: The Manner In Which α D−fsw Changes With Ph Forsupporting
confidence: 89%
“…The length of the resin bed was 1.5 cm. About 200 mg of brucite was first dissolved using a slightly excessive amount of boron-free HCl solution, passed through a column filled with Amberlite IRA 743 resin, and then eluted using approximately 5 ml of 0.1 M HCl at 75 • C. An amount of mannitol approximately equimolar to the boron content was added to the eluate, which was then desiccated to near dryness by partial evaporation in a super clean oven with laminar flow at 60 • C (Xiao et al, 2003). The solution was then loaded again into the column filled with a mixed resin composed of 0.5 ml cation-exchange resin (H + form) and 0.5 ml anion-exchange resin (ion-exchange II, HCO − 3 form).…”
Section: Separation Of Boron From the Samplesmentioning
confidence: 99%
See 3 more Smart Citations